PENGARUH PENGGUNAAN ELECTRONIC COMPONENT TESTER SEBAGAI MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA PROGRAM KEAHLIAN TEKNIK AUDIO VIDEO SMKN 1 SUMBAR - Delsina Faiza; Thamrin Thamrin; Ahmaddul Hadi (Jurnal Teknologi Informasi dan Pendidikan, 2017)
This study aims to determine the effect of the use of Electronic Component Tester as instructional media to the students' learning outcomes in Audio Video Techniques Program SMK N 1 Sumbar on basic competence classify passive and active components in electrical and electronic circuit. The research method used in this research, especially in the design of Electronic Component Tester is Research and Development (R & D) research, which consists of media design, validation, revision, product manufacture, and testing. After the learning media is validated, experimental research will be conducted where the Electronic Component Tester will be used as a learning medium for the students of Audio Video Technique SMKN 1 Sumbar in basic competence to classify passive and active components in electrical and electronic circuits. Prior to treatment, students were given a pre-test to determine initial ability. After being given the use of Electronic Component Tester as a learning medium, a post-test was done to determine the group's ability improvement. Pre-test results obtained an average value of 50.60, while the post-test results obtained an average value of 61.90. Learning outcomes after applied Electronic Component Tester learning media was Increased by 11.31 point. Result of calculation at significant level α = 0,05 got tcount > ttable that is 2,905> 2,056. It can be concluded there is improvement of student learning outcome after using instructional media Electronic Component Tester in basic competence classify passive and active component in circuit electrical and electronics students Audio Video Technique Program in SMK N 1 Sumbar. Keywords: Electronic Component Tester, Learning Media, Learning Outcomes.